2006
DOI: 10.1111/j.1365-3032.2006.00500.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemolymph levels of Schistocerca gregaria ion transport peptide and ion transport‐like peptide

Abstract: Titres of ion transport peptide (ITP) and ion transport-like peptide (ITP-L) in the haemolymph of the desert locust Schistocerca gregaria Forska˚l are investigated using a combination of enzyme-linked immunosorbent assay and reversed-phase high-performance liquid chromatography (HPLC). The estimated circulating levels of these two peptides are used to investigate their putative physiological roles. Haemolymph levels of ITP-L are significantly higher in fed and exercise-stressed locusts than in starved insects,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…ITP in Schistocerca gregaria has been shown to control ion and fluid transport across the ileum in vitro (Audsley et al, 1992). Audsley et al (2006) found that ITP-like peptide in S. gregaria was upregulated during feeding. Meredith et al (1996) had previously shown the presence of an active ITP in S. gregaria (Q26491) as well as a closely related protein (Q26492) named ITP long form (ITP-L), also referred to as ion-transport peptide-like, which was not active and contained an extended carboxy terminus.…”
Section: Feeding Diuresis and Myotropic Related Peptidesmentioning
confidence: 97%
“…ITP in Schistocerca gregaria has been shown to control ion and fluid transport across the ileum in vitro (Audsley et al, 1992). Audsley et al (2006) found that ITP-like peptide in S. gregaria was upregulated during feeding. Meredith et al (1996) had previously shown the presence of an active ITP in S. gregaria (Q26491) as well as a closely related protein (Q26492) named ITP long form (ITP-L), also referred to as ion-transport peptide-like, which was not active and contained an extended carboxy terminus.…”
Section: Feeding Diuresis and Myotropic Related Peptidesmentioning
confidence: 97%
“…After Dircksen et al, with permission (Dircksen et al, 2008). compared with the already mentioned feeding-related changes in ITP and ITPL titres were only observed about 5 to 7 days after ecdysis from the fourth to the fifth larval stages of S. gregaria (Audsley et al, 2006). Drexler and colleageus (Drexler et al, 2007) set out to measure CHH immunoreactivity and presumed ManseITP-like material (1) densitometrically in immunostained preparations of TN-PVOs and (2) in haemolymph by a noncompetitive ELISA (0.25-8 nmol l -1 range) before, during and after larval ecdysis from L4 to L5 stages of M. sexta.…”
Section: Possible Functions Of Itps and Itpls And Functional Morpholmentioning
confidence: 98%
“…Can the derived concepts be confirmed by in vivo studies, and are these the only physiological actions of both peptides? As a first step towards answering these questions, Audsley and colleagues (Audsley et al, 2006) undertook an important study to measure and identify the proposed circulating peptides SchgrITP and SchgrITPL in the CC and the haemolymph of fed (0.5-8 min and directly bled thereafter) and starved S. gregaria. The authors used enzyme-linked immunosorbant assays (ELISAs) with hapten antisera specifically discriminating SchgrITP (with the above-mentioned C1-antiserum) and SchgrITPL [with antisera raised against the SchgrITPL65-79 fragment; both antisera produced by Ring and colleagues (Ring et al, 1998)].…”
Section: Possible Functions Of Itps and Itpls And Functional Morpholmentioning
confidence: 99%
See 1 more Smart Citation
“…Ion transport peptide (ITP) in locusts (Schistocerca gregaria and Locusta migratoria) was identified based on its antidiuretic activity in the ileum (Audsley et al, 1992(Audsley et al, , 2006. ITP, released from the endocrine organs known as the corpora cardiaca (CC), stimulates the ileum to transport Cl À ion from lumen to hemolymph, thus forming an electrochemical gradient driving water resorption.…”
Section: Introductionmentioning
confidence: 99%